\(n^2+2n+6=n^2+4n-2n-8+14=n\left(n+4\right)-2\left(n+4\right)+14\)
\(=\left(n-2\right)\left(n+4\right)+14\)
Do \(\left(n-2\right)\left(n+4\right)⋮\left(n+4\right)\)
\(\Rightarrow14⋮n+4\)
\(\Rightarrow n+4\in\left(1;-1;2;-2;7;-7;14;-14\right)\)
\(\Rightarrow n\in\left(-3;-5;-2;-6;3;-11;10;-18\right)\)
n2 + 2n + 6 là bội của n + 4
=> n2 + 2n + 6 chia hết cho n + 4
Mà n + 4 chia hết cho n + 4
=> n ( n + 4 ) chia hết cho n + 4
=> n2 + 4n chia hết cho n + 4
=> ( n2 + 2n + 6 ) - ( n2 + 4n ) chia hết cho n + 4
=> n2 + 2n + 6 - n2 - 4n chia hết cho n + 4
=> 2n + 6 - 4n chia hết cho n + 4
=> -2n + 6 chia hết cho n + 4
Mà n + 4 chia hết cho n + 4
=> -2 ( n + 4 ) chia hết cho n + 4
=> -2n - 8 chia hết cho n + 4
=> ( -2n + 6 ) - ( -2n - 8 ) chia hết cho n + 4
=> - 2n + 6 + 2n + 8 chia hết cho n + 4
=> 2n - 2n + ( 6 + 8 ) chia hết cho n + 4
=> 0 + 14 chia hết cho n + 4
=> 14 chia hết cho n + 4
=> n + 4 thuộc Ư ( 14 )
=> n + 4 thuộc { 1 ; - 1 ; 2 ; - 2 ; 7 ; - 7 ; 14 ; - 14 }
=> n thuộc { - 3 ; - 5 ; - 2 ; - 6 ; 3 ; - 11 ; 10 ; - 18 }